Second IEEE Consumer Communications and Networking Conference, 2005. CCNC. 2005
DOI: 10.1109/ccnc.2005.1405187
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the DOCSIS 1.1/2.0 MAC protocol on TCP

Abstract: The number of broadband cable access subscribers in the United States is rapidly approaching 30 million. However there is very little research that has evaluated TCP/IP in modern cable environments. We have developed a model of the Data over Cable System Interface Specification (DOCSIS) 1.1/2.0 MAC and physical layers using the 'ns' simulation package.In this paper we show that the interaction of the MAC layer on downstream TCP web traffic leads to poor network performance as the number of active users grow. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In prior work we have shown that performance can deteriorate as the MAP time grows [28,29]. The contention request allocation strategy and the use of fragmentation, concatenation and piggybacking also have significant impact on system performance.…”
Section: The Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior work we have shown that performance can deteriorate as the MAP time grows [28,29]. The contention request allocation strategy and the use of fragmentation, concatenation and piggybacking also have significant impact on system performance.…”
Section: The Simulation Modelmentioning
confidence: 99%
“…In the second study conducted on the testbed we analyzed the throughput of a single "always on" TCP application. In previous work we concluded that the upstream channel of a DOC-SIS system, because of its inability to return ACK packets at a high rate [29], can become a bottleneck in the downstream transport of bulk data. We created a single TCP flow in the downstream direction on the testbed and observed a maximum TCP throughput of 3.6 Mbps.…”
Section: The Tcp Throughput Workloadmentioning
confidence: 99%